THE EPISTEMOLOGY OF THE ULAMA OF THE LANDS BELOW THE WINDS' IN THE TWENTIETH CENTURY: A Study of Minhāj al-Umniyya Fī Bayān ‘Aqīdat Ahl al-Sunnah wa al-Jamā‘a of Tuan Guru Abdul Jalil Jambi (TAJDID: Jurnal Ilmu Ushuluddin, 2020)
The arrival of Islam into the lands below the winds, the terminology used to designate the Malay-Indonesian world or the entire South East Asia, was inseparable from the influence of Māturidīyya and Ashāʿira in kalām. This influence was reflected in the translation works or the commentaries upon ʿAqāʾid al-Nasafī of Imam al-Nasafī in the seventeenth century. The eighteenth century and onwards also saw a rapid appearance of the translations, commentaries,ḥāshiya, and taʿlīq of Umm al-Barāhīn of Imam al-Sanūsī. In Jambi, in the early twentieth century, Tuan Guru Abdul Jalil synthesized the worldview of kalam of al-Māturidīyya and Ashāʿira in his work, Minhāj al-Umniyya fī Bayān ʿAqīdāt al-Ahl al-Sunna wa al-Jamāʿā. The result of his endeavor was an epistemology of kalām that was established upon the classical intellectual legacy of Islam. Amid the hegemony of the Western epistemology on the general modern epistemology and, specifically, that of Islam, this article attempts to discuss the epistemology of Tuan Guru Abdul Jalil in order to answer the bewilderment of the modern epistemology. After analyzing the work of Tuan Guru Abdul Jalil along with other relevant results, this article shows that the epistemology of Tuan Guru Abdul Jalil is powerfully relevant in the current debates about epistemology.Datangnya Islam ke ‘negeri bawah angin’, suatu istilah pada masa lalu yang merujuk kepada dunia Indonesia-Melayu atau Asia Tenggara secara keseluruhan, tidak terlepas dari pengaruh kalam Māturidīyyah dan Ashāʻirah. Hal ini tampak dari lahirnya karya-karya dalam bentuk terjemahan dan ulasan terhadap ʻAqāʼid al-Nasafī karya Imam al-Nasafī pada abad ke-17. Semenjak abad ke-18 dan seterusnya, muncul pula ulasan-ulasan terhadap Umm al-Barāhīn karya Imam al-Sanūsī dalam bentuk terjemahan, ḥāshiyah, taʻlīq dan sebagainya secara masif. Di Jambi, pada awal abad ke-20, ada Tuan Guru Abdul Jalil yang mensintesiskan antara kalam Māturidīyyah dan Ashāʻirah dalam karyanya Minhāj al-Umniyyah fī Bayān ʻAqīdat Ahl al-Sunnah wa al-Jamāʻah. Hasilnya, terbentuklah suatu epistemologi dalam bingkai kalam berlandaskan pada tradisi keilmuan Islam klasik. Di tengah hegemoni epistemologi Barat dalam bangunan epistemologi modern umumnya dan kajian keislaman khususnya, tulisan ini mendiskusikan epistemologi Tuan Guru Abdul Jalil untuk menjawab kerancuan-kerancuan epistemologis modern tersebut. Setelah menelaah karya Tuan Guru Abdul Jalil dan karya-karya yang relevan lainnya, tulisan ini menunjukkan bahwa epistemologi Tuan Guru Abdul Jalil masih sangat relevan dalam memberikan tawaran-tawaran epistemologis saat ini.